A database management system for water quality control in a river basin - Md. Ali, Zarina; Said, Salim (Universiti Putra Malaysia, 1999)
Water flowing in a river system, originates either directly from surface runoff, underground spring, ground water depletion, lakes or other water bodies. Because of the point of origin influences the composition of surface water, test results for the overall quality of the water often reveal its sources. The sources of these pollutants were mainly domestic, industrial and agricultural. The pollution of the river water restricts the usage of this water for several purposes and affects the aquatic life. Monitoring of the river water will help in controlling the water quality and reduce the pollution impact and enhance the environment for the aquatic life. Several methods and procedures were used to control river pollution. Mathematical modeling have been used for predicting the river water quality, usually supported by laboratory and field tests for these purposes. In this study, mathematical model called Surface Water Modeling System (SMS) will be used and a data base management system for a river basin to be developed. Besides that, (GIS) and MapInfo will prepare the mapping area. This study will take Taman Mayang, Petaling Jaya, Selangor as a study area. The data base management system is to base on the field monitoring and the laboratory test. Hydrologic monitoring for rivers will help in running the proposed database monitoring system.